Cancer patients' experience with a pharmacist‐led oral chemotherapy clinic: A qualitative descriptive study. Issue 1 (13th December 2022) - Hamner, Allison N.; Andrick, Benjamin; Mathur, Anupama; Gionfriddo, Michael R.
Abstract: Introduction: Geisinger in Danville, Pennsylvania, has pharmacist‐managed oral chemotherapy clinics that manage approximately 100 patients per day. Through a collaborative practice agreement with the provider, the pharmacist serves as a clinical extender to manage patients' oral oncolytics between provider visits. Previous studies have described the clinical and financial impact of a pharmacist‐driven oral chemotherapy clinic, yet there is a paucity of data regarding patients' perceptions of the care received in such clinics. Objectives: We aimed to conduct a qualitative, semi‐structured, and descriptive study to better understand the patients' perceived role of the pharmacist in their care, perceived benefits, and opportunities for optimization. Methods: Patients were prospectively sampled from clinic records in this single clinic study. Eligible patients must have a clinic visit between November 2020 and March 2021, be at least 18 years of age, and have at least six documented encounters with the clinic pharmacist within the last 6 months. Patients were excluded if they were residents of a nursing home or rehab if they required a professional caregiver, or if they had not personally talked with the pharmacist during at least four encounters within the previous 6 months. Results: Out of 110 screened patients, 36 met the inclusion criteria, and 21 completed the interview. Overall, patients described the oral chemotherapy pharmacist as knowledgeable, helpful, and considerate of their situation. When comparing the oral chemotherapy pharmacist to a community pharmacist, some patients felt the oral chemotherapy pharmacist provided more personalized care. One area of improvement identified by patients included improving the clarity and consistency of clinic phone calls. Conclusions: Based on the results of our thematic analysis, patients value the services provided in our pharmacist‐managed oral chemotherapy clinic; however, areas of improvement included how pharmacists communicate with patients regarding their care and the pharmacist's role within the care team.